Optimizing control of adsorption separation processes based on the improved moving asymptotes algorithm - Yonghui Yang; Xuebo Chen; Na Zhang (Adsorption Science & Technology)
We adopt the orthogonal collocation finite element method to solve an equilibrium diffusion model of a simulated moving bed chromatography separation process. We propose an optimization strategy based on the improved moving asymptotes algorithm to improve system performance indexes. By the triangle theory, we verify the feasibility of the improved moving asymptotes method. The simulation results illustrate that the improved moving asymptotes method converges quickly and results in uniformly distributed optimal solutions. This work aims to show that the simulated moving bed process can be dynamically controlled and optimized using an optimizing controller based on the method of improved moving asymptotes, facilitating the design and operation of a simulated moving bed.